2023
DOI: 10.1161/atvbaha.122.318290
|View full text |Cite
|
Sign up to set email alerts
|

Quartet of APOCs and the Different Roles They Play in Diabetes

Abstract: APOA1 and APOB are the structural proteins of high-density lipoprotein and APOB-containing lipoproteins, such as low-density lipoprotein and very low-density lipoprotein, respectively. The 4 smaller APOCs (APOC1, APOC2, APOC3, and APOC4) are exchangeable apolipoproteins; they are readily transferred among high-density lipoproteins and APOB-containing lipoproteins. The APOCs regulate plasma triglyceride and cholesterol levels by modulating substrate availability and activities of enzymes interacting with lipopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 85 publications
(125 reference statements)
1
6
0
Order By: Relevance
“…For example, APOC1 and APOC4 had lower abundances in the DAT group and are thought to be involved in triglyceride metabolism, although the function of endogenous APOC4 is not completely known. 31,32 APOC2 was also not statistically significant but trended higher in the DAT group, and high APOC2 levels have been associated with downregulation of plasma TGs in humans. 32 Since this study size is small, the trends in these non-significant apolipoproteins are also notable.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…For example, APOC1 and APOC4 had lower abundances in the DAT group and are thought to be involved in triglyceride metabolism, although the function of endogenous APOC4 is not completely known. 31,32 APOC2 was also not statistically significant but trended higher in the DAT group, and high APOC2 levels have been associated with downregulation of plasma TGs in humans. 32 Since this study size is small, the trends in these non-significant apolipoproteins are also notable.…”
Section: Resultsmentioning
confidence: 77%
“…31,32 APOC2 was also not statistically significant but trended higher in the DAT group, and high APOC2 levels have been associated with downregulation of plasma TGs in humans. 32 Since this study size is small, the trends in these non-significant apolipoproteins are also notable.…”
Section: Resultsmentioning
confidence: 77%
“…The similar FCRs of APOC3 and APOC2 are also consistent with previous studies in humans ( 29 , 30 ). All APOCs are exchangeable apolipoproteins, moving readily between APOB-containing lipoproteins and HDL ( 31 ). Indeed, human studies have shown that the FCRs for APOC3 associated with APOB lipoproteins versus HDL are very similar and that it therefore is as informative to evaluate APOC3 overall FCRs in plasma ( 29 , 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…APOC3 has two mechanisms of action in triglyceride and cholesterol metabolism, both related to slower clearance of TRLs ( 16 , 42 ). Although APOC3 was found to increase VLDL production and APOB secretion in one study ( 43 ), later studies showed that endogenous APOC3 does not act through increasing VLDL production ( 44 , 45 , 46 , 47 ).…”
Section: Apoc3 Pools and Lipid Metabolismmentioning
confidence: 99%
“…Cardiovascular outcome trials that include subjects with and without diabetes would be the next important step ( 80 ). Including participants with diabetes would be important also because there are inconclusive indications that APOC3 inhibition could improve insulin sensitivity ( 42 ). However, there are several important considerations.…”
Section: Clinical Implications and Future Directionsmentioning
confidence: 99%